Green Victimology Perspective the Law Number 32 of 2009 on Environmental Protection and Management - Angkasa Angkasa (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Green victimology refers to the study of victimology that focuses on victims of environmental harm. The object of this new study cannot be separated from the philosophical values that underlie the growth of green victimology. Through literature research based on secondary data, this research focuses on two studies. The first is about the philosophical foundations of green victimology and the second is about the perspective of green victimology in the Law Number 32 og 2009 on Environmental Protection and Management. Based on the results of the research, it can be stated that the foundation of green victimology ecocentrism which sees that the environmental entities have intrinsic value in virtue of their own interests apart from its instrumental or utilitarian value for humans. This is different from the values underlying the previous victimological study that was based on anthropocentrism. Ecocentrism has been adopted in the Law Number 32 of 2009 on Environmental Protection and Management.